2014
DOI: 10.1016/j.enconman.2013.11.021
|View full text |Cite
|
Sign up to set email alerts
|

New concept for energy storage: Microwave-induced carbon gasification with CO2

Abstract: Energy storage is a topic of great importance for the development of renewable energy, since it appears to be the only solution to the problem of intermittency of production, inherent to such technologies. In this paper, a new technology for energy storage, based on microwave-induced CO 2 gasification of carbon materials is proposed. The tests carried out in this study on different carbon materials showed that charcoal consumes the least amount of energy. Two microwave heating mechanisms, a single-mode oven an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…In this way high CO 2 conversion of 95% and process energy efficiency of 70% were achieved simultaneously [25] . This is an important step towards a commercially viable process to produce O 2 free CO gas from CO 2 and C. A question that could not be answered in our previous work was whether the high yield is simply due to heating the carbon to a high temperature by the thermal plasma, similar to the heating of the carbon by microwaves by Bermudez et al [23] , or excitation of the CO 2 by the plasma was responsible. To answer this question, we report here further studies on the plasma driven Boudouard reaction to elucidate the mechanism.…”
Section: Water (%)mentioning
confidence: 77%
See 4 more Smart Citations
“…In this way high CO 2 conversion of 95% and process energy efficiency of 70% were achieved simultaneously [25] . This is an important step towards a commercially viable process to produce O 2 free CO gas from CO 2 and C. A question that could not be answered in our previous work was whether the high yield is simply due to heating the carbon to a high temperature by the thermal plasma, similar to the heating of the carbon by microwaves by Bermudez et al [23] , or excitation of the CO 2 by the plasma was responsible. To answer this question, we report here further studies on the plasma driven Boudouard reaction to elucidate the mechanism.…”
Section: Water (%)mentioning
confidence: 77%
“…Recently, Bermúdez et al [23] investigated the Boudouard reaction of CO 2 flowed through a fixed bed heated by microwave induction. They tested four carbon materials, anthracite, activated carbon, charcoal and coke, and found that charcoal and activated carbon had the best reaction activity with CO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations